2022
DOI: 10.1038/s41415-022-4977-0
|View full text |Cite
|
Sign up to set email alerts
|

The 'five star' fallacy: an analysis of online reviews and testimonials of dental practices in Northern England

Abstract: Aims and objectives To develop a greater understanding of how dental practices in the UK utilise and promote patient reviews and testimonials. To compare and contrast the star ratings, levels of engagement and levels of identifiability by comparing those placed by patients on social media, review websites and search engines, to those placed on providers' own websites. To provide recommendations for future advertising guidance.Materials and methods All practices providing dental services in North East England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 24 This ban also exists in Australia, Canada, some states in the United States, Hong Kong, and Singapore, but not in the United Kingdom, where the use of testimonials and reviews by dentists is unregulated. 25 , 26 However, it can be seen that websites conceived by dentists are more likely to display testimonials (35% of websites) than websites designed by specialist website providers (1.4% of websites). This can be explained by the fact that many dentist-created websites use the Google Sites tool, which enables patient comments to be included from the Google platform.…”
Section: Discussionmentioning
confidence: 99%
“… 24 This ban also exists in Australia, Canada, some states in the United States, Hong Kong, and Singapore, but not in the United Kingdom, where the use of testimonials and reviews by dentists is unregulated. 25 , 26 However, it can be seen that websites conceived by dentists are more likely to display testimonials (35% of websites) than websites designed by specialist website providers (1.4% of websites). This can be explained by the fact that many dentist-created websites use the Google Sites tool, which enables patient comments to be included from the Google platform.…”
Section: Discussionmentioning
confidence: 99%
“…Testimonials are fundamentally different from reviews as they are normally given to a company themselves and are solicited and used by those companies in marketing to provide a more specific description of what went well with regards to the experience with a product or service, whereas reviews tend to be shorter and are given to third-party websites having more influence through their quantity and independence (Donnell et al, 2022). Experimental research in the healthcare sector has shown that the effect of persuasive messages in the form of personal testimonials can be more effective in increasing risk perception and intention to get vaccinated compared to presenting objective statistics (de Wit et al, 2008).…”
Section: Introductionmentioning
confidence: 99%